Growth hormone treatment does not augment the anti‐diabetic effects of liraglutide in UCD‐T2DM rats - Michael M. Swarbrick; Chad L. Cox; James L. Graham; Lotte B. Knudsen; Kimber Stanhope; Kirsten Raun; Peter J. Havel (Endocrinology, Diabetes & Metabolism, 2023)
Abstract Introduction The incretin hormone glucagon‐like peptide‐1 (GLP‐1) slows gastric emptying, increases satiety and enhances insulin secretion. GLP‐1 receptor agonists, such as liraglutide, are used therapeutically in humans to improve glycaemic control and delay the onset of type 2 diabetes mellitus (T2DM). In UCD‐T2DM rats, a model of polygenic obesity and insulin resistance, we have previously reported that daily liraglutide administration delayed diabetes onset by >4 months. Growth hormone (GH) may exert anti‐diabetic effects, including increasing β‐cell mass and insulin secretion, while disrupting GH signalling in mice reduces both the size and number of pancreatic islets. We therefore hypothesized that GH supplementation would augment liraglutide's anti‐diabetic effects. Methods Male UCD‐T2DM rats were treated daily with GH (0.3 mg/kg) and/or liraglutide (0.2 mg/kg) from 2 months of age. Control (vehicle) and food‐restricted (with food intake matched to liraglutide‐treated rats) groups were also studied. The effects of treatment on diabetes onset and weight gain were assessed, as well as measures of glucose tolerance, lipids and islet morphology. Results Liraglutide treatment significantly reduced food intake and body weight and improved glucose tolerance and insulin sensitivity, relative to controls. After 4.5 months, none of the liraglutide‐treated rats had developed T2DM (overall p = .019). Liraglutide‐treated rats also displayed lower fasting triglyceride (TG) concentrations and lower hepatic TG content, compared to control rats. Islet morphology was improved in liraglutide‐treated rats, with significantly increased pancreatic insulin content (p < .05 vs. controls). Although GH treatment tended to increase body weight (and gastrocnemius muscle weight), there were no obvious effects on diabetes onset or other diabetes‐related outcomes. Conclusion GH supplementation did not augment the anti‐diabetic effects of liraglutide.